Character strengths and social self-efficacy among university students in North Macedonia - Maja Korubin Kjorluka (University American College Skopje, 2020)
Positive psychology is an approach within psychology that takes seriously as a subject matter those things that make life most worth living. It calls for as much focus on strengths, as on weaknesses and as much attention to fulfilling the lives of healthy people, as to healing the wounds of the distressed. This research gives small contribution to the science of human wellbeing and happiness. It investigates the relationship between 24 character strengths and social self-efficacy among university students in North Macedonia. More concretely, the research investigates the relation between three character strengths profiles (strengths of the heart, strengths of the mind and other character strengths) and social self-efficacy. The sample consists of 239 first year university students from six faculties within the St. Cyril and Methodius University in Skopje. The following instruments are used for the research: VIA Inventory of Strengths and Self-Efficacy Scale. Results show that there is positive correlation between character strengths and social self-efficacy, which means that as the character strengths increase, social self-efficacy increases too. The only exception is the strength love of learning. According to the results, there is no statistically significant correlation between this strength and the social self-efficacy.
Keywords: 330; positive psychology; character strengths; VIA Classification of Character Strengths; social self-efficacy.